Effect of mutation in the aromatic amino acid pathway on sporulation of Saccharomyces cerevisiae. - Lucchini, G (1978)
Mutations in ARO1 and ARO2 genes coding for enzymes involved in the common part of the aromatic amino acid pathway completely block the sporulation of Saccharomyces cerevisiae when in a homozygous state, whereas mutations in all the other genes of the same pathway do not. This effect is not due to the lack of any intermediate metabolite but rather to the accumulation of a metabolite preceding chorismic acid. Shikimic acid or one of its precursors was identified as the possible inhibitor. The presence of the three aromatic amino acids in the sporulation medium restores the ability to undergo meiosis. This seems not to be due to a feedback inhibition of the first enzymes of the pathway but rather to a competition between aromatic amino acids and the inhibitor on a site specific for the meiotic process. The inhibition of sporulation seems to occur at a very early step in meiosis, as indicated by the lack of premeiotic DNA synthesis in aro1 and aro2 mutants.